Effectiveness of Learning Activities during the Covid-19 Pandemic - Risa Amalia (International Consortium of Education and Culture Research Studies, 2021)
This research article aims to analyze the effectiveness of learning activities implemented by MI Muhammadiyah 2 Kedungbanteng in the midst of the Covid 19 pandemic, namely online and offline. Of course, these two learning systems have similarities and differences, strengths and weaknesses both in the learning process and the effectiveness to be achieved. Qualitative research method with a descriptive approach based on field facts, namely a comparative study of offline and online learning. The results of the study and discussion show that there are differences between online and offline learning in terms of methods, media, and learning processes that complement each other in achieving basic competencies. There are several obstacles in the learning activities of these two systems, such as limited learning time because learning time is reduced so that the material presented is not optimal. If it is presented its effectiveness is only about 70%. That is why teachers and parents collaborate with each other to motivate students by giving interesting and fun assignments and all teachers make a video to provide energy and motivation for students even though they are only learning at home.